(untitled) (Research, Society and Development, 2021)
The species Carapichea ipecacuanha is a reference among medicinal plants with active principles of economic relevance due to the presence of two isoquinoline alkaloids: emetin and cephaline. Phenology being the branch of ecology considered fundamental for understanding the dynamics of plant communities and strategies for the sustainable use of species. The objective of this work was to register the phenophases of Carapichea ipecacuanha, correlating them with the climatic elements, in order to indicate the most suitable time for the collection and use of the plant material of the species. The frequencies were recorded weekly in the period from 2015 to 2019, the activity index, correlation between phenophases and climatic elements and percentages of days of phenophases were evaluated. The results show that the species, flora and fruit every month of the year, the phenological activity showed differences between accessions, the Spearman correlation index showed a significant correlation between fruiting and climatic factors. Variation in the pattern of occurrence of the number of days of flowering and fruiting was recorded between the accession groups, with the maximum number of days of flowering occurring in October and November, and fruiting with a peak especially in March and April. However, it is suggested the collection of plant material of the species for medicinal in the months of August and September, whose registration of the number of days that occur the phenophases undergoes reductions. It is pertinent to carry out further studies on the correlation of phenology with climatic events considering the each access performance individually.